COMMON FIXED POINT THEOREM IN INTUITIONISTIC FUZZY METRIC SPACE UNDER (S-B) PROPERTY - Sharma, P. K.; Sharma, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2012)
The main purpose of this paper is to give common fixed point theorem in intuitionistic fuzzy metric space under strict contractive conditions for mappings satisfying (S-B) property